Differentiation of functional constipation and constipation predominant irritable bowel syndrome based on Rome III criteria: a population‐based study. Issue 9 (4th March 2015) - Koloski, N. A.; Jones, M.; Young, M.; Talley, N. J.
Summary Background While the Rome III classification recognises functional constipation (FC) and constipation predominant IBS (IBS‐C) as distinct disorders, recent evidence has suggested that these disorders are difficult to separate in clinical practice. Aim To identify whether clinical and lifestyle factors differentiate Rome III‐defined IBS‐C from FC based on gastrointestinal symptoms and lifestyle characteristics. Method 3260 people randomly selected from the Australian population returned a postal survey. FC and IBS‐C were defined according to Rome III. The first model used logistic regression to differentiate IBS‐C from FC based on lifestyle, quality‐of‐life and psychological characteristics. The second approach was data‐driven employing latent class analysis (LCA) to identify naturally occurring clusters in the data considering all symptoms involved in the Rome III criteria for IBS‐C and FC. Results We found n = 206 (6.5%; 95% CI 5.7–7.4%) people met strict Rome III FC whereas n = 109 (3.5%; 95% CI 2.8–4.1%) met strict Rome III IBS‐C. The case–control approach indicated that FC patients reported an older age at onset of constipation, were less likely to exercise, had higher mental QoL and less health care seeking than IBS‐C. LCA yielded one latent class that was predominantly (75%) FC, while the other class was approximately half IBS‐C and half FC. The FC‐dominated latent class had clearly lower levels of symptoms used to classify IBS (pain‐related symptoms) and was more likely to be male (P = 0.046) but was otherwise similar in distribution of lifestyle factors to the mixed class. Conclusion The latent class analysis approach suggests a differentiation based more on symptom severity rather than the Rome III view.